Mahatma Gandhi and freedom struggle - Pruthi, R. K.; Chaturvedi, Archna (New Delhi Commonwealth, 2024)
Mahatma Gandhi had realised that freedom was not going to be achieved by violent means. He followed the path of intense search and deep meditation. Thus he developed art of fundamental commitment to 'Satya' and 'Ahimsa'. He unculcated a moral dedication to self chosen vows and sacrificial action. He thus devised a spiritual method and organizational style to prepare the nation to fight and win freedom from the strongest empirical power of the world. It is unique and fascinating experiment of gaining freedom. This book aims at selection of important and immovative material on different aspects of leadership, organisation and style of Mahatma Gandhi. How Gandhi prepared himself and the nation for this fight? How he created a mass movement. Why the colonial rulers gave way to his non-violent struggle for freedom.
Keywords: Mahatma Gandhi; India Independence